Effect of the Number of Gaussian Points and Their Distribution on Image Quality - Al-Hamdani, A. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This research involves studying the influence of increasing the number of Gaussian points and the style of their distribution, on a circular exit pupil, on the numerical calculations accuracy of the point spread function for an ideal optical system and another system having focus error of (0.25 A. and 0.5 A. ) It was shown that the accuracy of the results depends on the type of distributing points on the exit pupil. Also, the accuracy increases with the increase of the number of points (N) and the increase of aberrations which requires on increas (N).